IMPLEMENTASI METODE PICTURE AND PICTURE PADA PELAJARAN IPS KELAS IV DI MIS AL-ISTIQOMAH ATAR BAWANG BATU KETULIS LAMPUNG BARAT - Irawan, Asep (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
This research is motivated  by the activity and  learning out comes  in IPS lesson in MIS Al-Istiqomah Atar Bawang which is lower than other subjects. Initial observation s  provide an overview of what factors are causing  it to happen which one of them is still awake motivation in following the learning done by conventional methods.  Based  on the results obtained at the time of observation, the author is interested to conduct cooperative learning in accordance with the criteria. Keywords can consider learning method using image and  picture method and *inhibiting factor and supporting factor. This research method is qualitative research method by way of overcoming it. The data collected were analyzed by qualitative descriptive technique. The results obtained show how to draw pictures and pictures can improve student motivation in learning activities easier and not monotonous. Based on the results of the observations that have been done, it can be concluded the form of picture and image learning is very appropriate to be applied to fourth grade students MIS Al-Istiqomah. This of course will have a direct impact on. Therefore, it is expected that teachers are able to understand the ways and means of supporting cooperative learning methods in the form of Picture and Picture